Ginger-Derived Exosome-Like Nanoparticles Loaded With Indocyanine Green Enhances Phototherapy Efficacy for Breast Cancer - Guo Z; Li G; Shen L; Pan J; Dou D; Gong Y; Shi W; Sun Y; Zhang Y; Ma K; Cui C; Li W; et al. (International Journal of Nanomedicine)
Zhaoming Guo,1,2,* Guqing Li,2,* Lanjun Shen,2 Jiawei Pan,2 Danni Dou,2 Yuwei Gong,2 Wanwan Shi,2 Yuhua Sun,2 Yi Zhang,2 Kun Ma,2 Changhao Cui,2 Wenxin Li,3,4 Qiang Liu,5 Xudong Zhu1,4,6 1Department of General Surgery, Cancer Hospital of Dalian University of Technology, Cancer Hospital of China Medical University, Liaoning Cancer Hospital & Institute, Shenyang, Liaoning, 110042, People’s Republic of China; 2School of Chemical Engineering, Marine and Life Sciences, Dalian University of Technology, Panjin, Liaoning, 124221, People’s Republic of China; 3The second Department of Hepatopancreatobiliary Surgery, Cancer Hospital of Dalian University of Technology, Cancer Hospital of China Medical University, Liaoning Cancer Hospital & Institute, Shenyang, Liaoning, 110042, People’s Republic of China; 4Liaoning Provincial Key Laboratory of Precision Medicine for Malignant Tumors, Shenyang, Liaoning, 110042, People’s Republic of China; 5Faculty of Medicine, Dalian University of Technology, Dalian, Liaoning, 116024, People’s Republic of China; 6Department of Oncology, Shengjing Hospital of China Medical University, Shenyang, Liaoning, 110004, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xudong Zhu, Department of General Surgery, Cancer Hospital of Dalian University of Technology, Cancer Hospital of China Medical University, Liaoning Cancer Hospital & Institute, Shenyang, Liaoning, 110042, People’s Republic of China, Tel +86 13354204706, Email xdzhu@cmu.edu.cn; XudongZhu@uky.edu Qiang Liu, Faculty of Medicine, Dalian University of Technology, Dalian, Liaoning, 116024, People’s Republic of China, Email andyliu_1844@dlut.edu.cnPurpose: Phototherapy has remarkable advantages in cancer treatment, owing to its high efficiency and minimal invasiveness. Indocyanine green (ICG) plays an important role in photo-mediated therapy. However, it has several disadvantages such as poor stability in aqueous solutions, easy aggregation of molecules, and short plasma half-life. This study aimed to develop an efficient nanoplatform to enhance the effects of photo-mediated therapy.Methods: We developed a novel bio-nanoplatform by integrating edible ginger-derived exosome-like nanoparticles (GDNPs) and the photosensitizer, ICG (GDNPs@ICG). GDNPs were isolated from ginger juice and loaded with ICG by co-incubation. The size distribution, zeta potential, morphology, total lipid content, and drug release behavior of the GDNPs@ICG were characterized. The photothermal performance, cellular uptake and distribution, cytotoxicity, anti-tumor effects, and mechanism of action of GDNPs@ICG were investigated both in vitro and in vivo.Results: GDNPs@ICG were taken up by tumor cells via a lipid-dependent pathway. When irradiated by an 808 nm NIR laser, GDNPs@ICG generated high levels of ROS, MDA, and local hyperthermia within the tumor, which caused lipid peroxidation and ER stress, thus enhancing the photo-mediated breast tumor therapy effect. Furthermore, in vivo studies demonstrated that engineered GDNPs@ICG significantly inhibited breast tumor growth and presented limited toxicity. Moreover, by detecting the expression of CD31, N-cadherin, IL-6, IFN-γ, CD8, p16, p21, and p53 in tumor tissues, we found that GDNPs@ICG substantially reduced angiogenesis, inhibited metastasis, activated the anti-tumor immune response, and promoted cell senescence in breast tumor.Conclusion: Our study demonstrated that the novel bio-nanoplatform GDNPs@ICG enhanced the photo-mediated therapeutic effect in breast tumor. GDNPs@ICG could be an alternative for precise and efficient anti-tumor phototherapy.Keywords: ginger-derived exosome-like nanoparticles, phototherapy, indocyanine green, lipid peroxidation, ER stress